DIPLOMASI PUBLIK INDONESIA DALAM MENINGKATKAN INDUSTRI PARIWISATA OLAHRAGA DI ASIA PASIFIK: STUDI KASUS PT. DAMAI INDAH GOLF PERIODE 2015 - 2018 - Aldo Josua, (2021)
Sports tourism is one of the industrial sectors in the world that has an influence on the interest of tourists to come to travel to a country. The Asia Pacific region is one of the regions that has the second fastest growing sports tourism industry in the world. Indonesia, which is included in it, is committed to developing sports tourism with a combination of the wealth of natural tourism and indigenous Indonesian culture. The purpose of developing Indonesia's sports tourism potential is to create a positive image of Indonesian tourism, it will be in line with the country's economic growth and other aspects. Various efforts have been made by various parties such as from the Ministry of Tourism and Creative Economy of the Republic of Indonesia (Kemenparekraf RI) and other stakeholders. The role of the Indonesian Ministry of Tourism and Creative Economy is fully supported by the sports tourism industry players who are implementing it in the field, such as in the golf sports tourism industry. PT. Damai Indah golf is an example of Indonesian golf industry players synergizing with the Indonesian Ministry of Tourism and Creative Economy in the development of the sports tourism industry. The decline in tourists on a national scale in sports tourism, one of which was in the golf industry in 2016 was felt by PT. Damai Indah Golf and other golf industry players. The Ministry of Tourism and Creative Economy of the Republic of Indonesia and all stakeholders who are trying to restore the situation of the growth of foreign tourists to Indonesia for golf sports tours with public diplomacy efforts and successfully implemented. Public diplomacy efforts carried out by the Ministry of Tourism and Creative Economy of the Republic of Indonesia are contained in programs concerning the participation of the media and the international community specifically in the 2015 - 2018 period. Supporting data is also obtained from the efforts made by PT. Damai Indah Golf with the framework of public diplomacy. This study uses the dimensions of public diplomacy according to Joseph Nye's thoughts and the concept of Tourism by Jafar Jafari as the basis for its analysis. The research method used by the author in this thesis uses a qualitative approach with case studies and the type of research is descriptive-analytic.